Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai - Eka Lia Sinuraya; Veithzal Rivai Zainal; Lenny Christina Nawangsari (Publikasi Indonesia, 2022)
This study aims to determine the effect of work motivation on employee performance at the Personnel and Organization Bureau of the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration. The data collection method used for this research is a field study. The population in this study were employees at the Bureau of Personnel and Organization, Secretariat General, Ministry of Villages, Development of Disadvantaged Regions, Transmigration with a sample of 30 employees. Data collection was carried out using a questionnaire which was then processed using the SPSS 26 application. The results showed that work motivation has a significant and positive effect on employee performance. The research limitations only use one independent variable (work motivation) to measure performance, of course further research can replace or add other variables such as organizational culture, work relationships, employee income so that it can measure performance in more depth in order to create new findings in the field of human resource management.